การประยุกต์วิธีการวินิจฉัยมาลาเรียจากตัวอย่างปัสสาวะและน้ำลายเพื่อประเมินสภาวะของโรคมาลาเรียในเชิงระบาดวิทยา - จตุรงค์ พุทธพรทิพย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
Accurate species identification and sensitive detection of malaria parasites are the foundation of treatment and control of malaria, one of the most important infectious diseases of mankind. Microscopy detection with giemsa-stained blood films has been widely deployed for malaria diagnosis, enabling effective management in general clinical practice. However, a number of malaria-infected individuals may harbor low number of parasites in their circulation that could escape conventional microscopy detection threshold; thereby, a considerable number of malaria-related morbidity and mortality as well economic loss could ensue. Furthermore, morphological detection of malaria parasites in blood smears may not unambiguously and accurately identify malaria species besides a considerable variation in competency of microscopists. The advent of polymerase chain reaction (PCR)-based detection and speciation of malaria parasites in blood samples has circumvented limitation of microscopy detection. Importantly, application of PCR -based method has provided a possibility of using saliva and urine samples as alternative DNA sources for malaria diagnosis although the sensitivity remains inferior to that of conventional microscopy detection. Herein, we have devised PCR -based method for detection and identification of all five human malaria species targeting genes encoding cytochrome oxidase subunit I (PCR-COXI), cytochrome oxidase subunit III (PCR-COXIII and PCR-COXIII3 ) and cytochrome b (PCR-Cytb-New) of the mitochondrial genome. Comparative analysis has revealed that PCR-Cytb-New confers comparable diagnostic performance with PCR-Cytb previously developed by us. To assess and improve diagnostic sensitivity of using saliva and urine samples for malaria diagnsis, 502 febrile individuals who attended malaria clinics in Tak, Chiangmai, Chiangrai, Mae Hong Sorn and Chantaburi Provinces were recruited in this study. Of these, microscopy could detect 110 Plasmodium falciparum, 128 P. vivax and 3 co-infections of both species. By increasing volume of blood, saliva and urine samples to 200 III for DNA template preparation, PCR-Cytb from blood samples could clearly identify all five malaria species and 11 cases with mixed species infections whereas results from saliva samples yielded slightly more sensitive detection ofP.falciparum and P. vivax than microscopy. Although PCR results from urine samples were less sensitive than that from microscopy, the difference seems to be trivial that may not preclude using urine as an alternative DNA source for molecular diagnosis. Meanwhile, saliva and urine samples could be used to detect allelic diversity in the merozoite surface protein 2 locus of P.falciparum (PfMsp2) and the merozoite surface protein 1 locus of P. vivax (PvMsp1) in which 3D7 family of the former and Sal-1/Belem type b of the latter predominate in this study population. Despite the fact that allele typing of these loci using saliva and urine samples offered approximately 30% and 65%, respectively, less sensitive than using blood samples, alleleic distribution of these loci in the study population was remarkbly concordant regardless of the sources of samples used. Follow-up study of 17 P falciparum-infected patients and 18 P. vivax-infected patients has shown that malarial DNA could not be detected in blood, saliva and urine samples of these patients on day 7, 14,21 and 28 except two positive PCR results from blood samples on day 7 obtained from patients infected with P falciparum. It is likely that delayed clearance of malarial DNA occurred in these patients because subsequent negative PCR results were observed without additional antimalarial drug administration. Taken together, using a sensitive PCR detection and increasing volume of clinical samples enables saliva and urine samples be deployed as alternative DNA sources for diagnosing all five human malaria species as well as for determination of allelic distribution of malaria vaccine candidate genes. Further assessment of the methods described herein by recruiting larger scale of sample size will be required prior to general clinical implementation that will lead to novel non-invasive malaria diagnosis.